Medical physicists in Malaysia: A national workforce survey 2019 - Wong, Jeannie Hsiu Ding; Zin, Hafiz M.; Pawanchek, Mahzom; Ng, Kwan Hoong (Elsevier, 2019)
Objective: Medical physics in Malaysia is still considered a young profession. This workforce survey aims to understand the status, aspirations, motivation and experiences of medical physicists (MPs) in the country. A subsection of this survey also aims to understand the role of women. Method: A survey was carried out between April 20 and May 30, 2018 by a working group under the Medical Physics Division of the Malaysian Institute of Physics (IFM). The survey form was designed using Google Form and sent to various public and private institutions nationwide that employed MPs registered with IFM. Results: A total of 106 responses (28% men and 72% women) were analysed. This represented 30% of the medical physics workforce. Majority of them had postgraduate degrees, but their clinical training is mostly obtained on the job with no certification. The number of low-ranking female MPs was disproportionately high. MPs worked long hours and achieving work-life balance (WLB) was a challenge. Factors that improved their WLB included working close to home, having a supportive manager and flexible working hours. Most MPs aspired to become professional and mentor younger compatriots, besides contributing to patient care and research. Gender discrimination was reportedly low. Conclusion: Medical physics in Malaysia is growing and has a strong representation of women. In future, they would probably take over the top management from their male counterparts, whose number had stagnated. A united effort was essential to set up a proper clinical training system to train clinically qualified MPs. © 2019 Associazione Italiana di Fisica Medica